Trend Analysis of Air Quality Index in Catania from 2010 to 2014. (December 2015) - Lanzafame, R.; Monforte, P.; Patanè, G.; Strano, S.
Abstract: Information on air quality in urban areas represents an important objective to raise awareness and participation of citizens towards those measures aimed at containing and reducing vehicular traffic. For several years at the international level, evaluation procedures have been adopted by indices. One of the first synthetic indices, adopted by the United States Environmental Protection Agency (US-EPA), was the Pollution Standard Index (PSI). In 1999, the EPA replaced the PSI index with Air Quality Index (AQI), which includes two new sub-indices, the ozone at ground level and fine particulate. Despite the European Decisions 97/101/EC and 2001/752/EC, have established an exchange of information from networks and individual stations measuring ambient air pollution in Member States, the use of a single index has not yet been defined that allows you to compare different realities. This heterogeneity emerges in Italy as well, where only a few Environmental Protection Agencies disclose indexes to inform citizens. In this article, the Air Quality Index (AQI) currently used by the United States Environmental Protection Agency has been applied to the metropolitan city of Catania, in order to analyze the level of pollution daily from 2010 to 2014. Through the use of the AQI it was possible to synthesize in a single daily value, concentrations of major pollutants in urban areas (NO2, O3, CO, SO2, PM10 ) for the entire period. For the calculation procedure of the AQI, the data concentrations were provided by Municipal Ecology and Environment Office. The data relates to three monitoring stations, whose locations have not changed over the years. This also made it possible to evaluate the change in frequency of AQI agglomerations where the monitoring units have been positioned. The value obtained by the AQI for each station has been ranked in six levels of pollution; each level has been associated with a particular coloring allowing this information to be more intuitive. Lastly, it was possible to reach the air quality assessment in urban environment from the frequency variations of each level derived from the year 2010 until 2014.